The use of curesive audiovisual media as the right complementary feeding counseling media - Suminar, Ratna; Karim, Fatmawati; Purnamasari, Kurniati Devi; Hindiarti, Yudita Ingga; Ningrum, Widya Maya (Galuh International Journal of Community Service and Development, 2024)
Nutritional problems having a serious impact on the quality of human resource is still faced by Indonesian people. Malnutrition is caused by various factors both inside and outside of health problems. According to the World Health Organization (WHO), malnutrition has a role of 54% in infant and toddler mortality. Lack of nutritional intake during growth has consequences ranging from stunted growth, and impaired brain growth, to death. Nutrition has a big role in reducing the rate of illness and death, especially in infants and toddlers. Improper nutritional intake is still the cause of the high malnutrition and malnutrition in Ciamis Regency. Improper complementary feeding is the main cause of early malnutrition in infants under two years old. Lack of nutrient intake is greatly influenced by knowledge and behavior on the type of complementary feeding given. Curesive Audiovisual Media is an audiovisual health counseling media in the form of motion audiovisual with MP4 format inserted into a flash drive and an authentic cover named containing health messages regarding infant nutrition 0−24 months during the MP-ASI phase starting from the basic rules of feeding children, the requirements for MP-ASI according to WHO, and modification of complementary feeding formula for infants aged 6−24 months according to the age of the child.